Oral health status of Down's syndrome patients in Aseer, Saudi Arabia - N C Sandeepa; Sara Ali Al Hagbani; Fatmah Abdulrahman Alhammad; Amal Saeed Al Shahrani; Sara Eid Al Asmari (Wolters Kluwer Medknow Publications, 2021)
Introduction: It was observed that compared to the general population, mentally challenged subjects have higher rates of poor oral hygiene. Gingivitis is a common finding with moderate or severe variety reported most commonly. Periodontal disease is the most significant oral health problem, which can even lead to mobility of tooth and tooth loss. It is essential to generate oral health precautionary agendas and familiarize it with them. Materials and Methods: Four Centres of rehabilitation in the Aseer region of Saudi Arabia were included and subjects of 3-24 year age group was examined. Written informed consent was obtained from directors of Centres. Caries, oral hygiene status, soft-tissue and hard-tissue lesions were evaluated and statistically analyzed. Results: Higher Decayed, Missing and Filled Teeth score was observed in the present study in contrast to many other studies. Periodontal disease was seen in higher age group with higher percentages. Poor oral hygiene was seen in 27.3% of males and 66.7% of females. Tongue lesions comprised 85.7%, which accounted for the major part of soft-tissue abnormality. Various occlusal abnormalities (75%) and developmental tooth disturbances (53.6%) constitute the higher portion in hard-tissue abnormality. Conclusion: Dentists should be conscious of the range of oral anomalies that can manifest in this group of the patients. The microbial or serological investigation was not done which could have explained the etiology behind these lesions. In spite of these confines, the survey result have provided information regarding the oral health status of Down's syndrome subjects and the necessity of focusing on oral health need.